Nonlinear dynamics of pipeline with liquid in a vicinity of critical flow velocities - Limarchenko, O.; Vasilevskiy, Yu. (Vietnam Journal of Mechanics, 2008)
We developed the nonlinear model of pipeline dynamics with high-speed liquid motion. On the basis of the variational methods we constructed the nonlinear discrete model and numerical algorithm for investigation of problems of dynamics and dynamical stability of pipeline. We considered examples of dynamical behavior of the system for different velocities of liquid flowing, including the case of critical velocity of flow, when loss of straight line stability of pipeline is possible.